Desmoplastic Crosstalk in Pancreatic Ductal Adenocarcinoma Is Reflected by Different Responses of Panc-1, MIAPaCa-2, PaTu-8902, and CAPAN-2 Cell Lines to Cancer-associated/Normal Fibroblasts - Novák, Štepán; Kolář, Michal; Szabó, Arpád; Vernerová, Zdena; Lacina, Lukáš; Strnad, Hynek; Šáchová, Jana; Hradilová, Miluše; Havránek, Jan; Španko, Michal; Čoma, Matúš; Urban, Lukáš; et al. (Cancer genomics & proteomics, 2021)
BACKGROUND/AIM: Pancreatic ductal adenocarcinoma (PDAC) still represents one of the most aggressive cancers. Understanding of the epithelial-mesenchymal crosstalk as a crucial part of the tumor microenvironment should pave the way for therapies to improve patient survival rates. Well-established cell lines present a useful and reproducible model to study PDAC biology. However, the tumor-stromal interactions between cancer cells and cancer-associated fibroblasts (CAFs) are still poorly understood. MATERIALS AND METHODS: We studied interactions between four PDAC cell lines (Panc-1, CAPAN-2, MIAPaCa-2, and PaTu-8902) and conditioned media derived from primary cultures of normal fibroblasts/PDAC-derived CAFs (PANFs). RESULTS: When the tested PDAC cell lines were stimulated by PANF-derived conditioned media, the most aggressive behavior was acquired by the Panc-1 cell line (increased number and size of colonies, remaining expression of vimentin and keratin 8 as well as increase of epithelial-to-mesenchymal polarization markers), whereas PaTu-8902 cells were rather inhibited. Of note, administration of the conditioned media to MIAPaCa-2 cells resulted in an inverse effect on the size and number of colonies, whereas CAPAN-2 cells were rather stimulated. To explain the heterogeneous pattern of the observed PDAC crosstalk at the in vitro level, we further compared the phenotype of primary cultures of cells derived from ascitic fluid with that of the tested PDAC cell lines, analyzed tumor samples of PDAC patients, and performed gene expression profiling of PANFs. Immuno-cyto/histo-chemical analysis found specific phenotype differences within the group of examined patients and tested PDAC cell lines, whereas the genomic approach in PANFs found the key molecules (IL6, IL8, MFGE8 and periostin) that may contribute to the cancer aggressive behavior. CONCLUSION: The desmoplastic patient-specific regulation of cancer cells by CAFs (also demonstrated by the heterogeneous response of PDAC cell lines to fibroblasts) precludes simple targeting and development of an effective treatment strategy and rather requires establishment of an individualized tumor-specific treatment protocol.
Keywords: duktální karcinom slinivky břišní; Epithelial–mesenchymal interaction; nádorové mikroprostředí; fibroblasty; Cancer-Associated Fibroblasts; Cell Line, Tumor; Fibroblasts; Epithelial-Mesenchymal Transition; tumor stroma; Carcinoma, Pancreatic Ductal; tumor micro - environment; Pancreatic Neoplasms; pancreas; lidé; cancer stem cell; Humans; nádory slinivky břišní; fibroblasty asociované s nádorem; nádorové buněčné linie; Tumor Microenvironment; epitelo-mezenchymální tranzice